Molecular Research of Lipid Peroxidation and Antioxidant Enzyme Activity of Comamonas testosteroni Bacterial Cells under the Hexachlorobenzene Impact - Dimova, Mariia; Tugai, Andrii; Tugai, Tetiana; Iutynska, Galyna; Dordevic, Dani; Kushkevych, Ivan (International journal of molecular sciences, 2022)
The species of Comamonas testosteroni is the most common human pathogen of the genus, which can be associated with acute appendicitis, infections of the bloodstream, the peritoneal cavity, cerebrospinal fluid, inflammatory bowel disease, and in general, bacteremia. According to the literature, Comamonas testosteroni has destructive activity to a wide range of toxic chemical compounds, including chlorobenzenes. The specified strains were isolated from the soil of the organochlorine waste landfill, where hexachlorobenzene (HCB) was predominant. These strains were expected to be capable of degrading HCB. Microbiological (bacterial enrichment and cultivating, bacterial biomass obtaining), molecular biology, biochemical (enzymatic activities, malondialdehyde measuring, peroxidation lipid products measuring), and statistical methods were carried out in this research. The reaction of both strains (UCM B-400 and UCM B-401) to the hexachlorobenzene presence differed in the content of diene and triene conjugates and malondialdehyde, as well as different catalase and peroxidase activity levels. In terms of primary peroxidation products, diene conjugates were lower, except conditions with 20 mg/L HCB, where these were higher up to two times, than the pure control. Malondialdehyde in strain B-400 cells decreased up to five times, in B-401, but increased up to two times, compared to the pure control. Schiff bases in strain B-400 cells were 2-3 times lower than the pure control. However, in B-401 cells Schiff bases under higher HCB dose were in the same level with the pure control. Catalase activity was 1.5 times higher in all experimental variants, compared to the pure control (in the strain B-401 cells), but in the B-400 strain, cells were 2 times lower, compared to the pure control. The response of the two strains to hexachlorobenzene was similar only in peroxidase activity terms, which was slightly higher compared to the pure control. The physiological response of Comamonas testosteroni strains to hexachlorobenzene has a typical strain reaction. The physiological response level of these strains to hexachlorobenzene confirms its tolerance, and indirectly, the ability to destroy the specified toxic compound.
Keywords: Hexachlorobenzene; katalasa; Antioxidants; Schiff Bases; Schiff bases; Catalase; Chlorobenzenes; lipidy; diene and triene conjugates; lidé; chlorbenzeny; Lipids; peroxidace lipidů; catalase; Comamonas testosteroni; hexachlorbenzen; malondialdehyde; Lipid Peroxidation; Schiffovy báze; Malondialdehyde; antioxidancia; malondialdehyd; Soil; hexachlorobenzene; půda; peroxidase; Humans